Perancangan Pengembangan Kawasan Wisata Pemancingan Untuk Peningkatan Ekonomi Masyarakat Desa Jada Bahrin - Desy Yofianti; Yayuk Apriyanti; Ferra Fahriani; Endang Setyawati Hisyam; Revy Safitri (Universitas Lancang Kuning, 2022)
Jada Bahrin Village has a strategic location for the location of the development of fishing tourism areas because it is located on the outskirts of the Batu Rusa River channel. The development of fishing area tourism aims to increase the economic income of the village community and village government. Another goal of developing this area is so that Jada Barin Village can develop more because of the large number of tourists visiting. This service activity uses data collection methods and regional design or design. The document from the design of this fishing tourism area was welcomed by the village government for the basis of its development. The development of this fishing tourism area can later make Jada Bahrin Village more well developed.